Kualitas Madu Kelulut (Heterotrigona itama) Di Kota Palangka Raya: The Quality of Stingless Honey Bee (Heterotrigona itama) in Palangka Raya City - Muhammad D. Kesuma; Yetrie Ludang; Gimson Luhan; Alpian Alpian; Herry Palangka Jaya; Nuwa Nuwa; Yusintha Tanduh; Yosefin Ari Silvianingsih (JURNAL HUTAN TROPIKA, 2026)
The study aimed to evaluate and compare the quality of kelulut honey (Heterotrigona itama) from three cultivation locations in Palangka Raya City, namely Kelampangan (M1), Jalan Hiu Putih (M2), and Jalan Beliang (M3). The three locations have similar forage vegetation dominated by red calliandra, lemon santos, and bidara. The quality parameters tested included laboratory analysis (water content, reducing sugar, and acidity) and organoleptic tests (taste, aroma, color, and viscosity) with reference to SNI 8664:2018. The results showed that differences in cultivation locations significantly affected water content and acidity, but did not significantly affect reducing sugar content. Based on SNI 8664:2018, all samples met the water content standard (≤ 27.5%). However, in the acidity parameter, only locations M2 and M3 met the standard, while location M1 exceeded the threshold. The reducing sugar content at the three locations did not meet the minimum standard limit of 55%. Organoleptic test results showed that M2 honey excelled in aroma and flavor, M1 honey in color, and M3 honey in viscosity. Kelulut honey from all three cultivation locations received good consumer acceptance, with a minimum rating of "quite favorable."Keywords: Kelulut honey quality, SNI 8664:2018, organoleptic test